2014
DOI: 10.1080/10810730.2014.906521
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patient–Clinician Information Engagement and Information Seeking from Nonmedical Channels in Fruit and Vegetable Intake Among Cancer Patients

Abstract: Previous research suggests positive effects of health information seeking on prevention behaviors such as diet, exercise and fruit and vegetable consumption. The current study builds upon this research, and strengthens causal claims from it, by examining the lagged effect of patient-clinician information engagement (PCIE) on fruit and vegetable consumption as well as the indirect effect on the outcome through seeking information from nonmedical channels. The results are based on data collected from a randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Although studies have shown that physician engagement in information exchange for lifestyle behaviors can effectively and positively change behavior [8,9], some groups of survivors in our study were less likely to report having health behavior discussions, particularly older survivors and those with low education. Older survivors were less likely to report having at least one discussion of health promotion, and also less likely to discuss strategies to improve health and diet compared to younger survivors.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although studies have shown that physician engagement in information exchange for lifestyle behaviors can effectively and positively change behavior [8,9], some groups of survivors in our study were less likely to report having health behavior discussions, particularly older survivors and those with low education. Older survivors were less likely to report having at least one discussion of health promotion, and also less likely to discuss strategies to improve health and diet compared to younger survivors.…”
Section: Discussionmentioning
confidence: 65%
“…Survivors fall short of meeting dietary and physical activity recommendations [5-7] and have high risk for comorbid conditions. Given previous studies' findings that provider-delivered information is effective for encouraging healthy behaviors [8,9], promoting healthy behavior habits and sharing information on how to maintain overall health and wellness is especially important for this population both the primary care and oncology setting [10]. …”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal study of cancer patients, health-related information-seeking through multiple sources, including friends and family, is found to positively influence diet, exercise, fruit and vegetable consumption, and a change in lifestyle behaviors (Moldovan-Johnson et al, 2014). Through social interaction, information obtained motivates further information-seeking behavior with subsequent positive health behaviors through support from social networks .…”
Section: Health Care Activitiesmentioning
confidence: 99%
“…Given the effectiveness of practitioner‐delivered information for encouraging healthy lifestyle behaviours in cancer patients (Moldovan‐Johnson, Martinez, Lewis, Freres, & Hornik, ; Pinto, Papandonatos, & Goldstein, ), promoting health behaviour change in this population and providing information on how to improve health and lifestyle is important in oncology settings (Rock et al., ). Little is known about the information and support needs of patients who have completed active treatment for colorectal cancer and whether such patients receive advice on how to improve their health and lifestyle by the oncology team.…”
Section: Introductionmentioning
confidence: 99%